Factors influencing Saudi dental students' preference of amalgam or composite for posterior dental restorations - Sharat Chandra Pani; Mohammad Fawaz Al Abbassi; Abdulrahman Daham Al Saffan; Maged Abdulrahman Al Sumait; Ahmed Nassir Shakir (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study was to tabulate the factors effecting Saudi dental students' selection of a posterior restorative dental material and compare those factors between a private and a government dental school in Riyadh. Materials and Methods: The sample comprised of 267 students studying in both the private dental college (67 males, 75 females) and the government dental college (55 males, 70 females) in their last 3 years of clinical training. The students were administered a structured questionnaire specifically designed for the purpose after obtaining informed consent. Responses were compared between the students of each school using the chi-square and Mann-Whitney U test. Each student's responses to amalgam and composite were measured using the Wilcoxon signed rank test. Results: Overall composite resin was the material preferred by a majority of the students regardless of the type of school. Students in both the private and the government college were likely to give higher scores for composite than amalgam. A majority of students in both schools felt that amalgam could not be completely replaced with composite. When asked to list the main drawbacks of amalgam and composite most of the respondents answered lack of esthetics for amalgam, while they listed micro-leakage as the greatest drawback of composites. Conclusion: The findings of our study suggest that dental students in the Kingdom of Saudi Arabia seem to possess the ability to work confidently with posterior composite resins and seem to be comfortable in doing so; however, there is a significant difference in the factors influencing their choice of material.